Use the zero product property to find the value of x that makes the following statement true: 2 x (x-3) = 0

1 answer

The zero product property states that if the product of two factors is zero, at least one of the factors must be zero.

Given the equation:

\[ 2x (x - 3) = 0 \]

we can set each factor equal to zero:

  1. \( 2x = 0 \)
  2. \( x - 3 = 0 \)

Now, we solve each equation:

  1. For \( 2x = 0 \): \[ x = 0 \]

  2. For \( x - 3 = 0 \): \[ x = 3 \]

Thus, the values of \( x \) that make the statement true are:

\[ x = 0 \quad \text{and} \quad x = 3 \]